Forty hadith on leading the way - Ali, Mohammed Farid (IIUM Press, 2020)
This Forty Hadith Collection focusses on the four cardinal principles of “Leading the Way” the tagline of IIUM leadership. KhalÊfah (Stewardship), AmanÉh (Trust), Iqra’ (Knowledge), and RaÍmatan lil ÑÓlamÊn (Mercy for the worlds) are the ingredients for making balanced individuals (insan sejahtera). With acculturing these principles, educational leaders can empower people, preserve the planat, build prosperity, and foster peace. This forty hadith collection in relation to the four cardinal principles will open windows to the vast realm of leadership and transformation in tandem with the Islamic worldview.